Développer et réduires les expressions suivantes

E= (3a-1)²+(7a-1)(7a+1) F=(5-2a)²-(4a-3)² G= 2(1-4a)²+3(5a-1)(4+3a)

factoriser les expressions suivantes

H= 53x-1)² -(5x+7)(3x-1) I= 5x² -10x(4x-3) J =100x² -(5-4x)²

Merci

1

Réponses

2014-01-08T23:30:28+01:00
Bonsoir

E = (3a -1)² + (7a - 1)(7a + 1)
    = (9a² - 6a + 1) + (49a²  - 1)
    = 9a² - 6a + 1 + 49a² - 1 
    = 58a² - 6a

F = (5 - 2a)² - (4a - 3)²
   = (25 - 20a + 4a²) - (16a² - 24a + 9)
   = 25 - 20a + 4a² - 16a² + 24a - 9
   = -12a² + 4a + 16

G = 2(1 - 4a)² + 3(5a - 1)(4 + 3a)
    = 2(1 - 8a + 16a²) + 3(20a + 15a² - 4 - 3a)
    = 2 - 16a + 32a² + 60a + 45a² -12 - 9a
    = 77a² + 35a -10


H = (3x - 1)²  - (5x + 7)(3x - 1)
    = (3x - 1)(3x - 1)  - (5x + 7)(3x - 1)
    = (3x - 1)[(3x - 1)  - (5x + 7)]
    = (3x - 1)(3x - 1  - 5x - 7)
    = (3x - 1)(-2x - 8)

I = 5x²  - 10x(4x - 3)
  = 5x[x - 2(4x-3)]
   = 5x(x - 8x + 6)
   = 5x(-7x + 6)
 
J =100x²  - (5 - 4x)²
   = (10x)² - (5 - 4x)²
   = [10x + (5 - 4x)][10x - (5 - 4x)]
   = (10x + 5 - 4x)(10x - 5 + 4x)
   = (6x + 5)(14x - 5)